Redox fusion of metal particles using deep eutectic solvents. Issue 24 (7th March 2018) - Abbott, Andrew P.; Cihangir, Salih; Ryder, Karl S.
Abstract : Alternating anodic and cathodic current pulses have been applied to a metal powder on an electrode surface to fuse the particles together. It is shown that homogeneous films can be electroformed with different morphologies depending on the size of the powder and the experimental conditions. Abstract : Alternating anodic and cathodic current pulses have been applied to a metal powder on an electrode surface to fuse the particles together. It is shown that homogeneous films can be electroformed with different morphologies depending on the size of the powder and the experimental conditions.